Factor sustrato y cobertura en la germinacion y desarrollo inicial de patrones de cacao (Theobroma cacao L.) en vivero, finca experimental La Represa - Velalcazar Ramos, Kenny Alejandro (2019)
This investigation was carried out in the Experimental Farm "La Represa" owned by the State Technical University of Quevedo, located in the province of Los Ríos. The objective is to determine the factor and the coverage in the germination and the initial development of the cacao patterns (Theobroma cacao L.) In nursery. Where a completely randomized design with bifactorial arrangement (4 x 4) was used, the first factor substrates (Mountain soil, Charcoal, Balza Saw and Rooting) the second factor covers (Banana Leaf, Bijao Leaf, Cement Paper and Sarán), in 16 treatments and 4 repetitions, each experimental unit consisted of 20 funds located in rows of 10, a statistical analysis was made through the analysis of the variance ANDEVA and the means of communication were compared through the Test of Tukey (p <0.05). The variables germination percentage, plant height, stem diameter, number of leaves, root length and root volume were evaluated in a period of 60 and 90 days after sowing. The pressure factor of the upper plant, the height of the plant, the number of leaves, the length of the root and the volume of the root, as well as the coverage factor in the variable percentage of germination. The evaluated treatments gave as a result that the best substrate for the percentage of germination was mountain land + balsa sawdust + rooting and saran with 90%. Statistical significance was found (p <0.05) in the length of the root at 60 days.